Colonization of the newborn respiratory tract and its association with respiratory morbidity in the first 6 months of life: A prospective cohort study. (September 2022) - Nathan, Anna Marie; Chong, Kai Ning; Teh, Cindy Shuan Ju; Hng, Shih Ying; Eg, Kah Peng; de Bruyne, Jessie Anne; Muhamad, Anis Najwa; Adam, Quraisiah; Zaki, Rafdzah Ahmad; Razali, Nuguelis
Abstract: Objectives: We aimed to determine the association between newborn bacterial colonization and infant respiratory morbidity in the first 6 months of life. Methods: This prospective study included healthy newborn infants. Nasopharyngeal swabs performed within 72 hours of delivery were analyzed using polymerase chain reaction. We assessed cumulative respiratory morbidity of infants at 6 months. Results: A total of 426 mother-infant pairs were recruited. In 53.3% (n = 225) of newborns, Streptococcus pneumoniae (46%) and Staphylococcus aureus (7.3%) were isolated. None had Haemophilus influenzae nor Moraxella catarrhalis . At the age of 6 months, 50.7% of infants had experienced respiratory symptoms, 25% had unscheduled doctor visits, and 10% were treated with nebulizers. Colonization with S. pneumoniae was associated with reduced risk of any respiratory symptom (adjusted odds ratio [aOR] 0.39, 95% confidence interval [CI] 0.16, 0.50), unscheduled doctor visits (aOR 0.35; 95% CI 0.18, 0.67), and nebulizer treatment (aOR 0.23, 95% CI 0.07, 0.72) at 6 months. Pregnancy-induced hypertension was also associated with increased need for nebulizer treatment (aOR 9.11, 95% CI 1.43, 58.1). Conclusion: Colonization of the newborn respiratory tract occurred in 53% of infants. S. pneumoniae was the most common organism, and this was associated with a reduced risk for respiratory morbidity at 6 months of life.